Linguistic Surrogacy With Minimal Semantics Among the Dagomba of Ghana - Hudu, Fusheini (Frontiers in Communication, 2021)
This paper discusses critical questions on the processing of non-native surrogate languages of the Dagbamba (Dagomba) of Ghana. The Dagbamba use the fiddle, talking drum and double bell to encode speech in Hausa, Akan and other languages they do not speak. Fiddling and talking drums are integral to their festivals, funerals, the installation of chiefs and other cultural events. These instruments are used to entertain, praise, and send messages ranging from daybreak notifications to mobilizing people for war. The surrogate language they produce is a specialised language, interpreted mainly by people deeply rooted in their culture. It indicates nobility and statesmanship. While the performers and their patrons do not understand Akan or Hausa, they process and communicate with Akan and Hausa surrogate languages. The maintenance of the languages of performance is part of the practitioners’ desire to preserve the cultural heritage of Dagbamba. This raises questions about the acquisition of these surrogate languages, the level of accuracy of production and comprehension, the role of music in the processing and the implications of these for linguistic theory. These questions are discussed on the basis of data from recorded interviews of talking drummers and fiddlers. The overarching goal is to highlight the gaps in our understanding of language processing that surface in the study of surrogate language, when processing takes place with a poverty of grammatical content.